Experience capitalization: Resilience and productivity in the Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
CTA is committed to supporting the Pacific Island States to build resilience and improve incomes and nutrition outcomes, especially in rural agricultural communities. Since mid-2016, CTA has been implementing the “Promoting Nutritious Food Systems in the Pacific Islands” project, co-funded by the International Fund for Agricultural Development, IFAD, and run in partnership with the Pacific Islands Private Sector Organisation, PIPSO. Its goal is to strengthen the capacity of the Pacific Island governments, farmer and private sector organisations, and sub-regional institutions to develop strategies and programmes, as well as mobilize financing, that can increase poor rural people’s access to nutritious and healthy food.